Does tax simplification yield more equity and efficiency? An empirical analysis for Germany - Andreas Peichl; Clemens Fuest; Thilo Schaefer (Finanzwissenschaftliches Forschungsinstitut an der Universität zu Köln (FiFo Köln), 2006)
This paper investigates the impact of tax simplification on various indicators of the efficiency of the tax system and on the distribution of income. The analysis is based on a simulation model (FiFoSiM) using German income tax and household survey microdata. We model tax simplification as the abolition of a set of deductions from the tax base included in the German income tax system. We find that this form of tax base simplification leads to a reduction in the use of professional tax advice, a more equitable income distribution and an increase in tax revenue. If these measures are combined with a reduction of income tax rates to preserve revenue neutrality, the effects depend on the type of rate schedule adjustment. The combination with a flat rate tax implies redistribution in favour of very high incomes, and an overall increase in income inequality. Efficiency effects in terms of changes in marginal tax rates and labor supply effects are mixed. The combination with a rate schedule adjustment which preserves the directly progressive rate schedule yields a tax reform which reduces the inequality of after tax incomes. We conclude that tax simplification may improve the efficiency of the tax system without increasing inequality of after tax income.
Keywords: D3; H2; J22; 330; Income distribution; polarisation; tax simplification; flat tax